mannat di here is your answer of question no 36 and 37
36. 5^x-2 × 3^2x-3 = 135
5^x-2 × 3^2x-3 = 5 × 3³
so, 5^x-2 = 5¹
x-2 = 1
x=3
also,
3^2x-3 = 3³
2x-3=3
2x=6
x=3
37.(i) is in top see
or
(ii) (a²- b²)³ + (b²- c²)³ + (c²- a²) / (a-b)³ + (b-c)³ + (c-a)³
= a⁶- b⁶ + b⁶ - c⁶ + c⁶ - a⁶ / a³-b³ + b³-c³ + c³- a³
=1.....is your answer I think not sure...
Attachments:
![](https://hi-static.z-dn.net/files/db9/e60bca3f42a669b1bb666214737b9861.jpg)
Answers
Answered by
1
Answer:
you are right ok do it. all rights
Answered by
1
Answer:
I hope this is right answer
Similar questions